THE “NGOPI” TRADITION IN THE FRAMING OF ISLAMIC SOCIETY IN KARANG BARU SUB-DISTRICT, ACEH TAMIANG DISTRICT - Perkasa, Maulana Bagas; Harahap, Salahuddin (LPPM Univ. Ibn Khaldun Bogor, 2025)
The tradition of coffee gatherings has become a deeply rooted social phenomenon in the lives of the people of Karang Baru District, Aceh Tamiang Regency. This study aims to analyze how the coffee tradition shapes the identity of a moderate and inclusive Islamic society. The approach used combines sociology to understand the social dynamics formed through community interactions, and Sufism to explore the spiritual values reflected in this practice. The results show that the coffee tradition is not merely a space for social interaction, but also a means of internalizing Islamic values such as tolerance, compassion, and brotherhood. Through this practice, the community implicitly applies Sufi teachings such as humility (tawadhu'), sincerity (ikhlas), and Islamic brotherhood (ukhuwah Islamiyah) in daily life. Thus, the coffee tradition serves as a medium for fostering a harmonious Islamic character within the local socio-cultural context.